2020
DOI: 10.5812/archcid.84372
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 16srRNA Methylase Genes Among Non-ESBL and ESBL-Producing Klebsiella pneumoniae Isolates

Abstract: The aim of our study was to investigate mechanisms of aminoglycoside resistance in extended-spectrum beta-lactamases (ESBL)producing Klebsiella pneumoniae (K. pneumoniae) isolates from Iran. To this end, 154 clinical isolates of K. pneumoniae were collected from two hospitals in Ilam city, Iran. The Kirby-Bauer (agar diffusion) antibiotic testing method was used to determine the susceptibility pattern of the isolates against kanamycin, gentamicin, tobramycin, netilmicin and amikacin. Aminoglycoside acetyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the study of Iraj et al, the aac (3) IIa, aac (6) Ib, and rmtB genes were identified in 55.8%, 80.8%, and 1.9% of the isolates, respectively. e aac (3) Ia and armA were not found in any of the isolates [68]. In the previous studies from Spain by Elisenda et al, the most frequent AME genes in Enterobacteriaceae were aph (3) Ib (65.4%) and ant (3) Ia (37.5%) [69], whereas in the recent study, the most frequent AME genes in K. pneumoniae were ant (3) Ia (44%) followed by aac (6) Ib (32%) and aph (3) Ib (32%).…”
Section: Discussionmentioning
confidence: 88%
“…In the study of Iraj et al, the aac (3) IIa, aac (6) Ib, and rmtB genes were identified in 55.8%, 80.8%, and 1.9% of the isolates, respectively. e aac (3) Ia and armA were not found in any of the isolates [68]. In the previous studies from Spain by Elisenda et al, the most frequent AME genes in Enterobacteriaceae were aph (3) Ib (65.4%) and ant (3) Ia (37.5%) [69], whereas in the recent study, the most frequent AME genes in K. pneumoniae were ant (3) Ia (44%) followed by aac (6) Ib (32%) and aph (3) Ib (32%).…”
Section: Discussionmentioning
confidence: 88%